Literature Review: The Use of Justified Multiple-Choice Tests in Scientific Literacy at Elementary School Level - Tamarin, Vina; Widi Wisudawati, Asih (Elementary Teacher Education Program, Majalengka University, 2025)
Evaluation plays a crucial role in the learning process, particularly in assessing students' science literacy. Among various assessment methods, reasoned multiple-choice tests stand out as an effective tool because they not only determine whether answers are correct or incorrect but also uncover the reasoning behind students' choices. This allows educators to gain a clearer and deeper understanding of students’ comprehension and critical thinking skills related to science concepts, especially at the elementary school level. This study aims to systematically review existing literature on the application of reasoned multiple-choice tests in measuring science literacy among elementary school students. Employing a Systematic Literature Review (SLR) approach guided by the PRISMA framework, the study ensures a transparent and rigorous selection of relevant articles. Data collection involved gathering studies focused on science literacy and reasoned multiple-choice testing, which were then synthesized to draw meaningful conclusions. The data analysis process consisted of identifying, selecting, and extracting articles that met inclusion criteria, followed by thematic analysis to identify recurring patterns and key findings. The results of this review indicate that reasoned multiple-choice tests are widely regarded as an appropriate and effective method to comprehensively assess science literacy in elementary education, providing valuable insights into students’ knowledge and reasoning abilities.